The link between public debt and public investment in Tanzania - Maureen Were; Lorah Madete (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In a bid to realize its development aspirations, Tanzania has made concerted efforts to increase public investment, particularly in the last decade. A significant proportion of these investments are financed by contracting debt, manifested by the rapid accumulation of public debt, especially external debt, with a notable rise in debt-servicing obligations. In view of these developments, this study sought to investigate the relationship between public debt and investment in Tanzania. The empirical analysis was conducted using the autoregressive distributed lag estimation approach based on data for the period 1976-2020. The results show that an increase in external debt has a positive impact of boosting public investment. However, the lagged effect of external debt accumulation is negative in the long run. Arguably, this could be attributable to the need to service and repay the debt which, depending on the cost of debt servicing, limits the net resources available for additional investment. Thus, it is of essence to ensure optimal use of resources by prioritizing and enhancing efficiency of public investment. Additionally, other avenues of funding such as public-private partnerships and financial market development could be explored to reduce dependence on external debt.
Keywords: E20; E22; H60; H63; 330; public investment; Tanzania; public debt